Autonomous operation and control of photovoltaic/solid oxide fuel cell/battery energy storage based microgrid using fuzzy logic controller. (21st January 2016) - Vigneysh, T.; Kumarappan, N.
Abstract: In this paper, development and simulation of photovoltaic (PV), solid oxide fuel cell (SOFC) and battery energy storage system (BESS) based microgrid is presented. The microgrid system is operating in autonomous mode to serve the loads. To effectively control the microgrid voltage and frequency and to achieve smoother power flow control between the generation and consumption, voltage–frequency (V/F) control based on fuzzy logic controller (FLC) is proposed in this paper. Even though when there are sudden load variations in the system and fluctuations in PV output power, the microgrid voltage and frequency is effectively maintained within the limits by the proposed FLC. The main function of the BESS is to absorb/supply the excess/deficit power from the PV system and to keep the dc-link voltage of the voltage source converter (VSC) constant. SOFC is used as a backup generator and it is controlled to generate its rated power when the state of charge (SOC) of the BESS reaches its lower limit. The PV, SOFC and BESS are connected to a common dc bus through dc–dc power electronic converters. A three phase VSC is used to convert the dc to ac and to supply various ac loads. The PV, BESS and SOFC based microgrid system is simulated using Matlab/Simulink. To show the effectiveness of the proposed FLC over the conventional proportional-integral (PI) controller, the same system is simulated using PI controller and the necessary results are compared. Highlights: Dynamic model of PV/SOFC/BESS based autonomous microgrid is presented. SOFC is used as backup generator to provide the deficit power. Fuzzy logic controller is used to control the microgrid voltage and frequency. Response under varying environmental condition and sudden load changes are simulated.